Notes on anti-imperialism and pro-imperialism of Haya de la Torre in Repertorio Americano - Barrera Rivera, Dan Abner (2021)
This article is a critical approach to the Peruvian politician Víctor Raúl Haya de la Torre, based on his writings published in the Costa Rican journal Repertorio Americano between November 1924 and August 1955. We found 73 texts by the author and 29 texts by another authors. Due to Repertorio, Haya became internationally known as one of the most representative voices of anti-imperialism. But this position is only one face of the Peruvian politician.We discovered in these texts his radical transformation in favor of imperialism. This is a less known change that we are interested in analyze.